Slovak Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper provides a brief overview of Slovakia's transformation over this period. The note is divided into three parts. The first section offers some historical background on the run-up to EU accession. The paper also discusses the economic impact of EU accession and highlights the main challenges that Slovakia still faces. Although the first decade in the EU has seen successes, Slovakia faces important challenges to consolidate its position and close the gap with more advanced economies. A first long-term challenge is to shift from efficiency to an innovation-driven growth model. Actions to improve the business environment and domestic infrastructure could lay the foundations for stronger and more job-rich growth. In Slovakia, the high unemployment rate reflects the faulty working of three key mechanisms: the transition from school to work; the transition from unemployment back to employment; and mobility across regions. In order to address this situation, wide-ranging policies need to be implemented. The quality of education and training needs to be improved in order to better correspond to labor market needs. The ongoing reform of vocational education and training is a step in the right direction.